Manajemen Sistem Informasi Perlengkapan Dan Peralatan Bengkel Sepeda Motor Umum Skala UKM (Usaha Kecil Dan Menengah) berbasis Komputerisasi - Simaskot, Johar; Arief, Dodi Sofyan; Susilawati, Anita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Motorcycle repair shop management is to manage the motorcycle workshop to be effective and efficient. Good workshop management must also be supported by a properly administration, in order to record all the resources that become workshop assets. Moreover, the motorcycle workshop also conducts spare parts sales to complete the replacement needs of broken vehicle spare parts. This study aims to analyze and design a workshop information system for small and medium enterprises (SMEs) engaged in the field of repairing of motorcycle. Generally the SMEs motorcycle workshops in this research, still uses a simple management system and manually in presenting the data required by the workshop. This it make difficult and inconvenient for the owner of a small and medium-scale of motorcycle workshop. Sequence, it is necessary to optimize the management system and change the simpler manual system to be computerized. One way is by implementing the 5S (Sort, Straighten, Shine, Standardize, Sustain) methods and creating an information system that can manage equipment in SMEs scale of motorcycle workshops. Stages of the method in this study: (1) survey of general workshop management SMEs scale, (2) do analysis of data obtained during the survey and provides input for workshop management based on 5S method, (3) to design and create information systems and databases using PHP (Hypertext Preprocessor) as the programming language and MySQL as the database. By implementing 5S management and this information system can help streamline the services of SMEs scale of motorcycle workshops.Key Words: Motorcycle Workshop management, 5S Method, PHP, MySQL, Information System.